Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1073/pnas.0605841103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of protein orientation upon immobilization on biological and nonbiological surfaces

Abstract: We report on a rapid simulation method for predicting protein orientation on a surface based on electrostatic interactions. New methods for predicting protein immobilization are needed because of the increasing use of biosensors and protein microarrays, two technologies that use protein immobilization onto a solid support, and because the orientation of an immobilized protein is important for its function. The proposed simulation model is based on the premise that the protein interacts with the electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 50 publications
(44 reference statements)
2
44
0
1
Order By: Relevance
“…Recent simulation studies have shown that nonspecific and long-distance electrostatic interactions can facilitate protein recruitment to charged surfaces such as biomembranes (22). To determine whether the surface charge influences the direction of protein recruitment in an ex vivo environment into artificial membranes, we inserted a model membrane protein into bilayers formed by lipids with differently charged polar headgroups and determined the resulting protein orientation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent simulation studies have shown that nonspecific and long-distance electrostatic interactions can facilitate protein recruitment to charged surfaces such as biomembranes (22). To determine whether the surface charge influences the direction of protein recruitment in an ex vivo environment into artificial membranes, we inserted a model membrane protein into bilayers formed by lipids with differently charged polar headgroups and determined the resulting protein orientation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The isoelectric point (IEP) of the (F ab ) 2 fragment is often larger than that of the F c fragment and the whole antibody (20,21). Hence, in an intermediary buffer pH level condition [i.e., pH level between IEP of the (F ab ) 2 and IEP of the F c ], the (F ab ) 2 fragment is positively charged and the F c fragment is negatively charged (18,19). As a result, in this condition, the antibody molecule as a whole can be effectively modeled as an electric dipole, where the dipole moment vector is pointing from the negatively charged F c to the positively charged (F ab ) 2 .…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Previously, our group developed a simulation procedure to predict the orientation of a protein upon its immobilization on a solid-state support in presence of the electric field (18). To this end, exploiting the charge distribution and polarizability properties of various proteins may be possible.…”
mentioning
confidence: 99%
“…The flux densities are therefore given by been recently extended to study ion transport in OmpF porin ion channels [16] and orientations of proteins with respect to charged surfaces [17].…”
Section: The Termsmentioning
confidence: 99%